FACTORS ASSOCIATED WITH INAPPROPRIATE BLOOD PRESSURE IN HYPERTENSIVE PATIENTS - Anderson da Silva Rêgo; Victória dos Santos Laqui; Fernanda Gatez Trevisan; André Estevam Jaques; Rosana Rosseto de Oliveira; Cremilde Aparecida Trindade Radovanovic (Universidade Federal do Paraná, 2018)
Objective: assess the factors associated with inappropriate blood pressure in hypertensive patients monitored in the Family Health Strategy. Method: cross-sectional study, involving 417 people in Maringá, Paraná. The data were collected in the first semester of 2016, using the instrument satisfaction of hypertensive users with Primary Health Care services; using the questions related to the sociodemographic, nutritional and clinical profile. In the data analysis, descriptive and inferential statistics were applied. Results: most interviewees, 62.4% were elderly, 67.8% female and 55.2% retired/pensioner. Inappropriate blood pressure was associated with people over 59 years of age, retired/pensioners, moderately active, without practicing physical exercise and weakly oriented about the disease. Conclusion: the results signal the need to reorganize the work process, strengthening the orientations and health education for arterial hypertension patients.